An Overview of Telehealth in Total Joint Arthroplasty. Issue 1 (February 2021) - Windsor, Eric N.; Sharma, Abhinav K.; Gkiatas, Ioannis; Elbuluk, Ameer M.; Sculco, Peter K.; Vigdorchik, Jonathan M.
With the increase in technological advances over the years, telehealth services in orthopedic surgery have gained in popularity, yet adoption among surgeons has been slow. With the onset of the COVID-19 pandemic, however, orthopedic surgery practices nationwide have accelerated adaptation to telemedicine. Telehealth can be effectively applied to total joint arthroplasty, with the ability to perform preoperative consultations, postoperative follow-up, and telerehabilitation in a virtual, remote manner with similar outcomes to in-person visits. New technologies that have emerged, such as virtual goniometers, wearable sensors, and app-based patient questionnaires, have improved clinicians' ability to conduct telehealth visits. Benefits of using telehealth include high patient satisfaction, cost-savings, increased access to care, and more efficiency. Notably, some challenges still exist, including widespread accessibility and adaptation of new technologies, inability to conduct an in-person orthopedic physical examination, and regulatory barriers, such as insurance reimbursement, increased medicolegal risk, and privacy and confidentiality concerns. Despite these hurdles, telehealth is here to stay and can be successfully incorporated in any total joint arthroplasty practice with the appropriate adjustments.